Analisis Tingkat Kepuasan Siswa Terhadap Penggunaan Media Pembelajaran Digital Dalam Mata Pelajaran Fisika - Rosynanda Nur Fauziah; Anik Ghufron; Ali Muhtadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the level of student satisfaction with the use of digital learning media in physics lessons, the learning media used is Augmented Reality or what is usually called AR. AR is a technology that combines two-dimensional (2D) or three-dimensional (3D) virtual objects into a real environment in real-time, so that the virtual object seems to be part of that environment. In other words, AR enriches the real-world view with digital elements. It is important to understand that AR is not just an additional technological tool, but rather a new thing in learning so that students respond well to it. The research results concluded that the use and integration of AR technology in education, especially physics subjects, can make a major contribution to improving the quality of learning and overall student satisfaction.